The manifestations of Quranic intertextuality in the poem "Laylat al-Qadr" by Farghali - Zhour Chettouh (Social Empowerment Journal, 2021)
This research focuses on the manifestations of Quranic intertextuality in the poem "Laylat al-Qadr" by the Egyptian poet "Al-Farghali", which occupies a prominent poetic position among poets in the modern era., He is someone who influence from Holy Quran words Adjacent words words Anagramand overturned, or he used statements of the Quran without change in the poetry or sometimes slightly changed the verses of the Qur’an, This discusses examine the Intertextuality Quran in the poem “ laylat alqader” of “Farghaly”